Da’wah Strategies of Shaikh Azizur Rahman Nesarabadi to Establish Unity in Diversity in Bangladesh: A Global Viewpoint - Huq, Fayzul; Islam, Arshad; Khatun, Kazi Afifa (European Journal of Applied Sciences, 2022)
This research demonstrates the daʽwah strategies of Shaikh Azizur Rahman Nesarabadi which he adopted to bring a unity in diversity in the multifaceted Muslim society of Bangladesh. Shaikh Nesarabadi was an Islamic scholar, social reformer, dāʽī, politician, and spiritual leader of Bangladesh. Throughout his entire life, he dedicated himself to establish the unity among Muslim political and non-political parties and different national daʽwah movements. For this reason, he established an Islamic party called Jamiyat Hizbullah, whose motto was al-Ittihad Ma al-Ikhtilaf (unity within diversity). The research has explored his major steps taken to bring all Muslims, especially the Islamic parties under one umbrella of Islam. This study examines his daʽwah strategies, concepts, and his role in the society and politics of Bangladesh by textual analysis of primary and secondary data. The findings of this research concern intellectual strategy, journalism and editing, and the founding of educational institutions. These include the establishment of Jamiyat Hizbullah, Hizbullah Jamiyatul Muslihin, Hizbullah Anti-corruption Committee, Council for an Ideal Society, Imad Fund, Herbal Treatment Committee, building a Self-reliant Nation, Moderation Movement of Ramadan, and the Cottage Industry Movement, which continue his legacies and contributions to bring unity in diversity.